BABINE: An original and user-friendly scale for the simple and quick management of herb-drug interactions in clinical practice - Anthony Cnudde; Camille Allely; Natacha Biset; Pierre Champy; Nathalie Fouilhé; Fanny Huret; Sibi Lawson; Aline Mercan; Doris Pascale Noukela Noumi; Serge Michalet; Andrea Montis; Stephanie Pochet; et al. (BMC Complementary Medicine and Therapies, 2024)
Abstract Background While more and more people tend to use herbal products thinking they are safer than conventional western medicine, the reality is other. If natural products are bio-active and possess potential therapeutic activities, then the benefit/risk balance should be considered like any other health product. Some herbs are known to have the potential to interact with patient’s treatment and to cause adverse drug reactions. While these are scarce, they are potentially harmful, and can lead to major sequels and even death in some cases. Despite these known facts, little guidelines about how to evaluate the risk of interaction and to handle them exist in literature. Notably, few scales allowing to assess the risk of a specific combination of herbs and drugs exist. Method We propose a new scoring method BABINE (Boosting Analysis of Bibliography for herb- drug INteraction Evaluation) and discuss a scale to evaluate this risk based on iterative rounds of experts’ discussion. Results After 6 rounds of case reports/clinical studies evaluation, we analyzed and synthesized criteria identified as important by the experts and developed a corresponding evaluation scale. Conclusion Even if our scale greatly simplifies pharmacological events, we believe it provides a robust and transparent way to rapidly assess the risk of adverse event.